Comparative Analysis of the Effectiveness Between Malwarebytes and BitDefender to Prevent Malware Attacks - Mohammad Zidan Yohanza; Muhammad Giat; Muhammad Iksan Fadhilah; Mohammad Sulaeman; Ibrahim Dafi Iskandar; Yuyun Hidayat (International Journal of Quantitative Research and Modeling, 2024)
Malware is the largest type of cyber-attack case in Indonesia. With the number of cases of malware occurring, many emerging software that provides services to ward off malware attacks. It takes the most effective anti-malware software to ward off malware attacks, so research is carried out. This study tested the detection and removal power of two anti-malware software (BitDefender and Malwarebytes). The initial research method used is to make a Pilot test which is a prefix in malware testing. In the Pilot test, the initial testing process for anti-malware software is carried out. Software that tested in the Pilot test include Malwarebytes, BitDefender, Avast, Cybereason, AVG, Avira. In the Pilot test, as many as 30 malwares were tested to determine which two software had the highest percentage of detection and removal tests. Furthermore, the data from the previous test got analyzed using the proportion of two populations test to determine the most effective software. With the tests of 500 malwares, it was found that the proportion of detection and removal of the BitDefender software is better than the Malwarebytes software. Therefore, it can be concluded that the BitDefender software is more effective than the Malwarebytes software as seen from the results of the test of the proportion of malware detection and removal.